2021
DOI: 10.1111/anec.12825
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification after acute myocardial infarction by amplitude–frequency mapping of cyclic variation of heart rate

Abstract: Background: Bluntedcyclicvariationofheartrate(CVHR),measuredasadecrease in CVHR amplitude (Acv), predicts mortality risk after acute myocardial infarction (AMI).However,AcvalsocanbereducedinmildsleepapneawithmildO 2 desaturation.WeinvestigatedwhetherAcv'spredictivepowerforpost-AMImortalitycould be improved by considering the effect of sleep apnea severity. Methods: In24-hrECGin265,291participantsoftheAllostaticStateMappingbyAmbulatoryECGRepositoryproject,sleepapneaseveritywasestimatedbythefre-quencyofCVHR(Fcv)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Also, while the average Fcv was higher in the supine position than in the left lateral and prone positions, the night-to-night In this study, an algorithm of the auto-correlated wave detection with adaptive threshold was used to detect CVHR and Fcv was used to estimate AHI. The usefulness of the CVHR as a maker of sleep apnea has been reported by many researchers (Arikawa et al, 2020;Guilleminault et al, 1984;Hayano et al, 2011;Hsu et al, 2020;Magnusdottir & Hilmisson, 2018;Shimizu et al, 2015;Yatsu et al, 2021), and the accuracy of AHI estimation by Fcv has been confirmed by several earlier studies (Hayano et al, 2011(Hayano et al, , 2013(Hayano et al, , 2020(Hayano et al, , 2021. In a study of 864 polysomnographic subjects with suspected sleep apnea, patients with AHI > 15 were detected with a sensitivity of 83% and specificity of 88% by using Fcv > 15 cph as a criterion (Hayano et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Also, while the average Fcv was higher in the supine position than in the left lateral and prone positions, the night-to-night In this study, an algorithm of the auto-correlated wave detection with adaptive threshold was used to detect CVHR and Fcv was used to estimate AHI. The usefulness of the CVHR as a maker of sleep apnea has been reported by many researchers (Arikawa et al, 2020;Guilleminault et al, 1984;Hayano et al, 2011;Hsu et al, 2020;Magnusdottir & Hilmisson, 2018;Shimizu et al, 2015;Yatsu et al, 2021), and the accuracy of AHI estimation by Fcv has been confirmed by several earlier studies (Hayano et al, 2011(Hayano et al, , 2013(Hayano et al, , 2020(Hayano et al, , 2021. In a study of 864 polysomnographic subjects with suspected sleep apnea, patients with AHI > 15 were detected with a sensitivity of 83% and specificity of 88% by using Fcv > 15 cph as a criterion (Hayano et al, 2011).…”
Section: Discussionmentioning
confidence: 69%
“…These studies also reported that the classification performance of Fcv was unaffected by older age (≥ 65 years), obesity, hypertension, diabetes mellitus, dyslipidemia, or the type of sleep apnea (obstructive or central) (Hayano et al, 2011(Hayano et al, , 2013. The merit of this method is that it requires only a single-lead ECG (Hayano et al, 2021;Hsu et al, 2020;Magnusdottir & Hilmisson, 2018), and in the present study, by applying this method to long-term ECG data, we were able to delineate the night-to-night dynamics of sleep apnea.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation